Análise da resistência de união à dentina de diferentes sistemas de retentores de fibra de vidro - Delevatti, Danielli Davanso (2023)
In this study, seek to evaluate the bonding resistance (BS) to dentin and the fail mode of prefabricated fiberglass seals (GFPs), including a universal system, which adapts to the diversities of root conduits, and custom retainers, compared to the root level. Thirty roots were prepared for rehabilitation with the GFPs, according to the indication for each reconstruction technique (n=10): group technique of the prefabricated retainer (CT), group technique of the prefabricated retainer anatomized with composite resin (ANA) and group technique of the universal system Splendor® (SPL – Angelus Ind. Bras.). After cementation, 2 specimens of each root third were obtained, and the BS was determined by means of the push-out test and the fail mode evaluated by means of and stereomicroscopic analysis. The result of ANOVA to two criteria showed a statistically significant difference when considering the independent variables system (p<0,001) and root third (p<0,001). The interaction between the variables was not statistically significant (p=0,259). From the statistical point of view, there was similar performance of the ANA and SPL groups in the three thirds evaluated, which were statistically superior to the TC group. The analysis of the fail mode, regardless of the root third, showed that the TC group presented significant difference in relation to the ANA and SPL groups, which presented statistically significant similarity among last third (p<0,05). A high percentage of mixed failure could be observed, followed by adhesive and cohesive failure. Within the limitations of this study and considering that the SPL system presented BS values similar to the techniques already used in clinical practice, we can consider its use for reconstruction of endodontically treated teeth with extensive coronary destruction and that therefore require intraradicular anchorage, since it requires fewer clinical steps